Catalytic and Noncatalytic Upgrading of Oils - Dalai, Ajay K., editor 645589; Dadyburjor, Dady B., editor 645590; Zheng, Ying, editor 645591; Duan, Aijun, editor 645592; Roberts, William L., editor 372322; Nanda, Sonil, editor 645593 (Washington, DC : American Chemical Society, 2021)
Achieving New Frontiers in Fuel Efficiency. Catalysis in industrial synthesis of fuels and chemicals accounts significantly toward global material production. Developing efficient processes and catalytic methods for the sustainable production and utilization of clean fuels and platform chemicals is the focus of this work. Expert editors have invited and developed specific articles that outline new frontiers in noncatalytic and catalytic pathways including catalyst synthesis, characterization, performances, reaction kinetics, and modeling, as well as applications of catalysts for the production of ultra-low-sulfur diesel fuels, clean fuels, fine chemicals, and other green products. Researchers and policymakers in energy will find this work useful.